Selfie dan Media Sosial pada Seni Sebagai Wujud Eksistensi - Raditya, Michael HB (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This article discusses the existence of individuals that are constructed based arts events. Selfie and social media in arts as a form of existance is the right word to respons upon the development of society. There is a issues would be discuss in this article; discuss about elements of arts existence, commodification of arts, and patterns of consumption. Literature review and ethnography is the method to solve the problem, with qualitative research. The restult of this article are; selfie is the new practice of arts consumption, social media as a field of existence, arts became a major commodity in society. The exchange not only enjoy arts object, but also there is technology that aims to increase its existence. Social media is new field for society to show the existence, and when someone selfie with art, would be more prestige. Arts became exist with a different way.